2023
DOI: 10.1186/s40246-023-00463-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational and mitochondrial functional studies of novel compound heterozygous variants in SPATA5 gene support a causal link with epileptogenic encephalopathy

Abstract: The SPATA5 gene encodes a 892 amino-acids long protein that has a putative mitochondrial targeting sequence and has been proposed to function in maintenance of mitochondrial function and integrity during mouse spermatogenesis. Several studies have associated homozygous or compound heterozygous mutations in SPATA5 gene to microcephaly, intellectual disability, seizures and hearing loss. This suggests a role of the SPATA5 gene also in neuronal development. Recently, our group presented results validating the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…These phenotypes are strikingly similar those associated with alleles in other components of the AIRIM complex, including AFG2A, AFG2B, and CINP [19][20][21][22]24,25,31 and are predominantly associated with global developmental delay, intellectual disability, muscular hypotonia, limb spasticity, dystonia, microcephaly, infantile seizures, as well as hearing and vision impairment (see Figure S1E for comparative summary). Importantly, patients that carry AFG2A and AFG2B allelic variants commonly exhibit similar neuroimaging features [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenotypes are strikingly similar those associated with alleles in other components of the AIRIM complex, including AFG2A, AFG2B, and CINP [19][20][21][22]24,25,31 and are predominantly associated with global developmental delay, intellectual disability, muscular hypotonia, limb spasticity, dystonia, microcephaly, infantile seizures, as well as hearing and vision impairment (see Figure S1E for comparative summary). Importantly, patients that carry AFG2A and AFG2B allelic variants commonly exhibit similar neuroimaging features [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have further implicated human AFG2A and AFG2B in ribosome production 17,18 . Strikingly, human genetic studies have identified a growing number of allelic variants in AFG2A, AFG2B, and CINP that are specifically associated with a range of NDDs, including intellectual disabilities, seizures, hearing loss, and microcephaly [19][20][21][22][23][24][25] . Here, we identify new variants in AIRIM associated with a similar range of neurological phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Мутации в гене SPATA5 связаны с микроцефалией, умственной отсталостью, судорогами и тугоухостью, что заставляет выдвинуть предположение о роли гена SPATA5 не только в сперматогенезе, но и в развитии нейронов и росте аксонов, и имеют аутосомно-рецессивный тип наследования [16]. Дефицит SPATA5 приводит к уменьшению количества митохондрий, в связи с чем уменьшается продукция АТФ на окончаниях аксонов и нарушается аксоногенез [14,15].…”
Section: клинический случайunclassified